2002
DOI: 10.4141/a01-091
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of STAT5A and STAT5B in mammary parenchymal tissue from Upton-Meishan and Large White gilts

Abstract: . 2002. Expression levels of STAT5A and STAT5B in mammary parenchymal tissue from Upton-Meishan and Large White gilts. Can. J. Anim. Sci. 82: 507-518. The implication of STAT5A and STAT5B in mammary gland development and maintenance of lactation is well documented in rodents and humans. However, little is known regarding their roles in mammary gland development during gestation in pigs. We identified and analyzed the complete coding sequences of swine STAT5A and STAT5B and evaluated their mRNA levels in mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
(59 reference statements)
1
15
0
Order By: Relevance
“…The negative association between STAT5A and PRL-R mRNA levels in the LW breed may be explained by the fact that STAT5B, and not STAT5A, mRNA levels are associated with mammary gland development in this breed (Palin et al 2002). Positive associations between leptin receptor mRNA levels and WAP, STAT5A and STAT5B are seen in the UM breed only.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The negative association between STAT5A and PRL-R mRNA levels in the LW breed may be explained by the fact that STAT5B, and not STAT5A, mRNA levels are associated with mammary gland development in this breed (Palin et al 2002). Positive associations between leptin receptor mRNA levels and WAP, STAT5A and STAT5B are seen in the UM breed only.…”
Section: Discussionmentioning
confidence: 80%
“…STAT5A and STAT5B mRNA levels were reported in Palin et al (2002). In the overall, as well as in the LW and UM gilt populations, significant correlations were observed between PRL-R mRNA levels and WAP, leptin (significant only in overall and LW), leptin receptor, STAT5A and STAT5B mRNA levels.…”
Section: Correlations Among Mrna Levels Of the Studied Genes In Parenmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, these differences may also be associated to prolactin-regulated genes, namely STAT5A and STAT5B, that are important in the development of the mammary glands. Indeed, Palin et al (2002) found that the expression level of STAT5A in mammary glands on day 110 of gestation was greater in Meishan than in Large White gilts, while mRNA expression levels for STAT5B were similar in both breeds.…”
Section: Teat Number and Mammary Developmentmentioning
confidence: 99%